Typological Peculiarities of Organizational Identity as Employee’s Individual Creation - Frolova, Olena (Psychological Prospects Journal, 2016)
Frolova O. V. Typological Peculiarities of Organizational Identity as Employee’s Individual Creation. The article grounds the actuality of the organizational identity phenomenon study. The author used her own survey to apply the data cluster analysis. Owing to that method, organizational identity types with different internal structure connections of the organizational identitydiagnostic indices have been figured out. The research defines that employees, who have the “emotionally-adaptable” type of organizational identity are characterized with a low level of consistency of their personal goals and aims with values of their organizations. But as far as they have a clearly defined positive appraisal of their belonging to the organization and thanks to the high level of their motivational needs satisfaction in frames of it, the employees try to adapt and follow the declared behavioral norms. The employees with the “cognitive-normative” type of an organizational identity closely identify themselves with their organization, demonstrate their high level of declarative knowledge about the general basics of their company functioning and its staff. But they rarely take an active part in their organizations’ life. The typological feature of employees, who have the “affiliative” identity type, is high level of satisfaction of their need in affiliation. In particular, that is about their friendly relations with their team members, understanding and support from their colleagues, positive emotions from the communication with their co-workers. The “cognitive-adaptable” identity type is marked by clear understanding of his belonging to the organization by the individual. At reflex level he positions himself as an integral part of it. At the same time, the low level of interiorization of values and aims of the organization combines with the attempts to adapt to behavior norms, accepted by the company. The “mature” organizational identity of the employees means the high development of all of its components at the cognitive, emotional and behavioral levels. The “immature” identity according to its content is an antipode to the “mature”. It is characterized with the low values of all of the diagnostic indices.